Determinants of enhanced vulnerability to coronavirus disease 2019 in UK patients with cancer: a European study. (June 2021) - Pinato, David J.; Scotti, Lorenza; Gennari, Alessandra; Colomba-Blameble, Emeline; Dolly, Saoirse; Loizidou, Angela; Chester, John; Mukherjee, Uma; Zambelli, Alberto; Aguilar-Company, Juan; Bower, Mark; Galazi, Myria; et al.
Abstract: Background: Despite high contagiousness and rapid spread, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to heterogeneous outcomes across affected nations. Within Europe (EU), the United Kingdom (UK) is the most severely affected country, with a death toll in excess of 100, 000 as of January 2021. We aimed to compare the national impact of coronavirus disease 2019 (COVID-19) on the risk of death in UK patients with cancer versus those in continental EU. Methods: We performed a retrospective analysis of the OnCovid study database, a European registry of patients with cancer consecutively diagnosed with COVID-19 in 27 centres from 27th February to 10th September 2020. We analysed case fatality rates and risk of death at 30 days and 6 months stratified by region of origin (UK versus EU). We compared patient characteristics at baseline including oncological and COVID-19–specific therapy across UK and EU cohorts and evaluated the association of these factors with the risk of adverse outcomes in multivariable Cox regression models. Findings: Compared with EU (n = 924), UK patients (n = 468) were characterised by higher case fatality rates (40.38% versus 26.5%, p < 0.0001) and higher risk of death at 30 days (hazard ratio [HR], 1.64 [95% confidence interval CI, 1.36–1.99]) and 6 months after COVID-19 diagnosis (47.64% versus 33.33%; p < 0.0001; HR, 1.59 [95% CI, 1.33–1.88]). UK patients were more often men, were of older age and have more comorbidities than EU counterparts (p < 0.01). Receipt of anticancer therapy was lower in UK than in EU patients (p < 0.001). Despite equal proportions of complicated COVID-19, rates of intensive care admission and use of mechanical ventilation, UK patients with cancer were less likely to receive anti–COVID-19 therapies including corticosteroids, antivirals and interleukin-6 antagonists (p < 0.0001). Multivariable analyses adjusted for imbalanced prognostic factors confirmed the UK cohort to be characterised by worse risk of death at 30 days and 6 months, independent of the patient's age, gender, tumour stage and status; number of comorbidities; COVID-19 severity and receipt of anticancer and anti–COVID-19 therapy. Rates of permanent cessation of anticancer therapy after COVID-19 were similar in the UK and EU cohorts. Interpretation: UK patients with cancer have been more severely impacted by the unfolding of the COVID-19 pandemic despite societal risk mitigation factors and rapid deferral of anticancer therapy. The increased frailty of UK patients with cancer highlights high-risk groups that should be prioritised for anti–SARS-CoV-2 vaccination. Continued evaluation of long-term outcomes is warranted. Highlights: Coronavirus disease 2019 (COVID-19) mortality in the United Kingdom (UK) has exceeded that of all other European countries. Outcomes of UK patients with cancer and COVID-19 may compare unfavourably with European countries. This is the first study to report detrimental outcomes for UK patients with cancer. UK patients are older, have more comorbidities and are less likely to have received COVID-19 therapy. Considering our results, rapid vaccination against severe acute respiratory syndrome coronavirus 2 should be recommended.